Study of Plant Growth as a Result of Revegetation in Coal Ex-Mined Land Pt. Arutmin Indonesia Site Batulicin South Kalimantan - Cecep Kusmana; Yadi Setiadi; Muhammad Abdul Lathif Al-Anshary (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2013)
Soil characteristic on ex-mined land of coal generally has high acidity, solid texture, and has fitotoxic compound that causes plant dwarfishness. This research observed correlation between soil characteristic with plant diversity on revegetation area of ex-mined land of PT. Arutmin Indonesia Site Batu Licin, South Kalimantan. This research was done with measure height and diameter of plant Acacia mangium and Falcataria moluccana that planted 1 year and six months ago from 28 plots and also analysis of chemical and physical soil features from each plot. The result of this research found a dwarfishness on half revegetation plants in this research location, and as a factor that has real correlation with plant diversity.Keywords: Acacia mangium, Falcataria moluccana, ex-mined land, revegetation